IMPROVING INVENTORY MANAGEMENT TO PREVENT SHORTAGE WITHIN SUGAR TRADE (The Indonesian Journal of Business Administration, 2019)
This study aims to solve the stock out problem that occurred in the company PT. Cakra Regla Mundial as a startup in the sale and distribution of white sugar by improving inventory policy.This out of stock is based on sugar demand which is not proportional to the availability of sugar supply due to the lack of production from PG Rajawali II West Java as a sugar producer in West Java so that the supply of sugar distributors is disrupted. Therefore, to deal with these problems there is a solution to meet the demands of this company by regulating the number and time of purchase it can meet the market that has been obtained by the company.With various factors that are difficult to predict, the calculation of sugar is narrowed based on historical demand to determine Inventory starting with predicting demand for 2019-2020 based on demand data in 2018-2019 namely by using time series prediction techniques and then proceed by selecting according to find the smallest error value. Furthermore, we found a simple exponential smoothing ? = 0,1 with smallest error value.After analyzing and doing calculations, some conclusions can be drawn, namely the best method that can be done by PT. Carkra Regla Mundial is a time series forecasting method by comparing MAPE, MAD, MSD errors, respectively 42, 16631, 3897388 with the process through minitab. What happened then was continued with the process of building inventory management by comparing existing inventory management to compare the smallest expenditure or inventory with the highest level of efficiency through the MRP technique, which is to determine the time and number of purchases vulnerable the total expenditure can be calculated on the lot-sizing system technique. In this technique, there is a comparison between existing inventory, lot-for-lot, EOQ and. furthermore it is concluded that EOQ is the most efficient technique with the lowest expenditure among other techniques, amounting to IDR 6,745,023 with the same demand and carrying cost is assumed to be constant.Keywords : Inventory Management, Shortage, Sugar, Stock